CTNI-15. PHASE 0/I TRIAL OF MYCOPHENOLATE MOFETIL COMBINED WITH RADIATION TO OVERCOME GLIOBLASTOMA TREATMENT RESISTANCE BY TARGETING DE-NOVO PURINE METABOLISM: INTERIM REPORT. (12th November 2021) - Umemura, Yoshie; Sun, Yilun; Junck, Larry; Leung, Denise; Kim, Michelle; Al-Holou, Wajd; Sagher, Oren; Heth, Jason; Schipper, Matthew; Lyssiotis, Costas; Marini, Bernard; Lawrence, Theodore; et al.
Abstract: BACKGROUND: De novo purine synthesis promotes glioblastoma growth and stemness, invasiveness, and resistance to chemoradiation. Mycophenolate mofetil (MMF) is an FDA-approved inhibitor of de novo purine synthesis that sensitizes glioblastoma to radiation and chemotherapy in mice. This Phase 0/I trial of MMF with Radiotherapy in Recurrent Glioblastoma (NCT04477200) aims to determine the maximum-tolerated dose of MMF that can be combined with radiation, and the extent to which the active metabolite of MMF accumulates in brain tumors and inhibits de novo purine synthesis. METHODS: Key eligibility criteria are age ≥18, KPS score ≥60%, and recurrent glioblastoma or gliosarcoma with clinical indication for re-irradiation (phase I) or re-resection/biopsy (phase 0). Patients with tumors involving ≥3 lobes or leptomeningeal space or bevacizumab use within 8 weeks are excluded. MMF 500-2000mg PO BID is given one week pre-operatively in Phase 0 (N=8), and up to 2000mg PO BID (starting 1000mg) on TITE-CRM dose escalation on Phase 1 cohort (N=30). RESULTS: Since 7/2020, three Phase 0 and six Phase I subjects have been enrolled. On the phase I cohort, 1500mg BID dose has been reached. Studyrelated toxicities have been limited to mainly grade 1-2 nausea and fatigue. No notable study related hematotoxicity have been noted. Additionally, mass spectrometry-based correlative measurements of the activity of de novo GTP synthesis are ongoing. CONCLUSION: MMF has been well tolerated up to 1500mg BID combined with radiotherapy in recurrent glioblastoma patients in this interim analysis. An additional upfront glioblastoma cohort with MMF with standard of care will activate in 2021. These studies will determine the maximum tolerated dose of MMF in combination with radiation and chemotherapy and provide a preliminary efficacy estimate at that dose. Encouraging results would support a randomized clinical trial to determine efficacy of MMF combined with chemoradiation in glioblastoma, and to define potential biomarkers for effectiveness.